Use of lepironia articulata (grey sedge) for treatment of domestic household wastewater - Nurul Najihah, Ashharudin (2019)
Water contaminated by human, chemical or industrial wastes can cause a number of diseases through ingestion or physical contact. Water-related diseases include diarrhea, gastric and fever. This final year project studied mainly about the use of Lepironia Articulata for treatment of domestic household wastewater. The objectives of this study were to analyse wastewater generated from a domestic household wastewater in University Malaysia Pahang, Gambang campus and to evaluate suitability and effectiveness of treating effluent by using Lepironia Articulata and compare the result with Malaysia Standard. The selected water quality parameter for this study were pH, biochemical oxygen demand (BOD), chemical oxygen demand (COD), turbidity, total suspended solids (TSS), oil and grease, cadmium, copper and lead. All of these parameters results were referred to as Environmental Quality Act, 1974. The experiment was conducted with two methods which are in-situ and ex-situ. The in-situ method was done at the site located in cafeteria college resident. Ex-situ was done at the FKASA Environment Laboratory, Universiti Malaysia Pahang. Sample A which contains 100% wastewater and plant. Sample B 70% wastewater, 30% distilled water and plant. Sample C contains 50% wastewater, 50% distilled water and plant. All the sample volume are 10L. Every week the data for every parameter was taken and recorded. After 3 weeks of observation, the percentage of removal were calculated. According to the data, Sample C shows the highest efficient removal percentage. For pH, the reading form acid become neutral, ammonia-nitrogen with 100%, COD with 78.70 %, BOD with 40% and oil and grease with 67.85%. Lastly, for heavy metal, there are 3 types of heavy metal that had been observed. For lead with 81.13%, cadmium with 56.25% and copper with 60.26%. Thru this study, the result shows that these plant is effective in treating ammonianitrogen, lead and copper since the percentage is more than 70%.